2022
DOI: 10.3390/metabo12100938
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Activity of Bioactive Phloroglucinols from the Rhizomes of Dryopteris crassirhizoma on Escherichia coli β-Glucuronidase: Kinetic Analysis and Molecular Docking Studies

Abstract: Phloroglucinols—one of the major secondary metabolites in Dryopteris crassirhizoma—exhibit various pharmacological effects, such as antiviral, antioxidant, and antidiabetic activities. This study evaluated 30 phloroglucinols isolated from the rhizomes of D. crassirhizoma for their inhibitory activity on β-glucuronidase via in vitro assays. Among them, dimeric phloroglucinols 13–15 moderately inhibited β-glucuronidase, and trimeric phloroglucinols 26–28 showed strong inhibitory effects, with IC50 values ranging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…This study highlights the potential health benefits of the metabolites found in B. karatas fruits [7]. Then, Phong et al (2022) isolated eight known secondary metabolites, including two isocoumarins and six coumarins, from the stems and branches of Acer mono Maxim. Their structures were confirmed using nuclear magnetic resonance spectroscopy and comparing the results to published reports.…”
mentioning
confidence: 82%
“…This study highlights the potential health benefits of the metabolites found in B. karatas fruits [7]. Then, Phong et al (2022) isolated eight known secondary metabolites, including two isocoumarins and six coumarins, from the stems and branches of Acer mono Maxim. Their structures were confirmed using nuclear magnetic resonance spectroscopy and comparing the results to published reports.…”
mentioning
confidence: 82%
“…Thus, this compound was tested at different concentrations to determine its IC 50 value. Previous studies reported that trimeric phloroglucinol nortrisflavaspidic acid ABB (2) exhibited the significant inhibition of PTP1B and β-glucuronidase, with IC 50 values of 1.19 ± 0.13 and 8.0 ± 1.8 µM, respectively [5,6]. In this study, nortrisflavaspidic acid ABB (2) demonstrated a strong inhibitory effect against α-glucosidase, with an IC 50 value of 34.0 ± 0.14 µM, stronger than that of the positive control acarbose (IC 50 = 329.2 ± 0.35 µM).…”
Section: Inhibitory Activity Against α-Glucosidasementioning
confidence: 99%
“…Dryopteris crassirhizoma Nakai is a semi-evergreen plant that is widely distributed in China, South Korea, and Japan; the root of this plant is used in the Chinese Pharmacopoeia to cure viral disease and verminosis [1]. Recent studies revealed many pharmacological effects of this plant such as anti-cancer, antioxidant, anti-inflammatory, protein tyrosine phosphatase 1B (PTP1B), and β-glucuronidase inhibitory activities [2][3][4][5][6]. Previous phytochemical investigations of the rhizomes of D. crassirhizoma demonstrated the presence of various components, including phloroglucinols, flavonoids, and triterpenes [5,6].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In Asian countries, natural products and herbal medicine have a longstanding history of being utilised for the treatment of various diseases because of their safety and low risk of side effects 11 . Nutmeg ( Myristica fragrans Houtt.…”
Section: Introductionmentioning
confidence: 99%